Implementation of Linear Congruential Generator (LCG) Algorithm, Most Significant Bit (MSB) and Fibonacci Code in Compression and Security Messages Using Images - Elveny, M; Syah, R; Jaya, I; Affandi, I (Journal of physics. Conference series, 2020)
The use of technology makes information spread more quickly compared to conventional methods that humans used before they knew technology. However, there is information that is only intended for certain people or institutions because the information is very confidential. The obstacle in exchanging information is the problem of information / data security. Because of that, an electronic message security algorithm which is quite well-developed is cryptographic (cryptography) and steganographic (steganography) algorithms. The development of increasingly advanced technology and the addition of more and more computer users also cause data to accumulate and transfer data from one device to another. The data is generally compressed first so that the exchange process does no take too long. Therefore, we need a system that can secure messages while reducing image data to be more efficient in the process of transmission and delivery. To implement this problem the system is designed using the Linear Congruential Generator (LCG) algorithm and the Most Significant Bit (MSB) as a security medium and using the Fibonacci Code algorithm as compression of the image. In implementation the system has a weakness in compressing images that not dominate colors because the size of the data becomes larger. In addition, the compression ratio on the variation of text length has decreased and has increased in the image variation experiments where if the compression ratio decreases, indicating better compression.